Simultaneous multidopant investigation of rare-earth-doped optical fibers by an ion microprobe - Sidiroglou, F.; Huntington, S.; Roberts, A.; Stern, R.; Fletcher, Ian; Baxter, G. (Optical Society of America, 2006)
The relative distribution of five elements present in the core area of several optical fiber samples has been obtained by utilizing nanoscale-secondary ion mass spectrometry. A strong correlation between the rare-earth (RE) ion and aluminum was observed, consistent with aluminum's improving the solubility of the RE ion. The central dip in distribution was less severe than that observed for germanium, characteristic of the collapse process during fabrication of the fiber preform.